Impact of Innovation on Consumers Liking and Willingness to Pay for Traditional Sausages - Żakowska-Biemans Sylwia; Sajdakowska Marta; Issanchou Sylvie (Polish Journal of Food and Nutrition Sciences)
The main objective of the study was to evaluate Polish consumers’ liking and willingness to pay for innovations in traditional sausages “Kabanos”. The study also attempted to determine whether regional differences may influence acceptance of innovations and the willingness to pay for such products. As both sensory factors and prices are important in food choice decisions, the methodological approach combined hedonic liking and experimental auctions. The study involved 221 consumers of traditional pork sausages who evaluated intrinsic and extrinsic product attributes in blind (tasting only), expectancy (product information only) and fully informed (tasting and product information) experimental conditions. The results show that acceptance of innovation in traditional sausages is determined by the type of innovation proposed. Innovation related to extrinsic attributes like packaging i.e. biodegradable packaging seem to be the most welcome regardless experimental conditions while innovations improving healthiness of traditional sausages but violating their sensory properties i.e. lower salt level tend to be disapproved. There are regional differences observed in acceptance and willingness to pay for innovative variants of Kabanos. In general, consumers in Warsaw are more inclined to pay more for innovative variants of Kabanos than consumers in Cracow. Participants from the two regions had also different hedonic reactions towards organic and spicy variant of Kabanos. Prior research concerning acceptance of innovation in traditional food products in Poland is scarce. Therefore, such information is particularly pertinent to SMEs and distributors operating in traditional food sector to support innovation and development of adequate communication strategies.